1998
DOI: 10.1074/jbc.273.35.22305
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-mediated Inactivation of Peptide Deformylase

Abstract: Peptide deformylase catalyzes the removal of the Nformyl group from newly synthesized polypeptides in prokaryotes. Its essential character and unique presence in prokaryotes make it an attractive target for antibacterial chemotherapy. However, purification and characterization of the peptide deformylase have remained a major challenge because this enzyme is extraordinarily labile under a variety of conditions (t 1/2 ϳ1 min at room temperature Protein synthesis in prokaryotes initiates with an N-formylmethionyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 22 publications
3
101
0
Order By: Relevance
“…1). Our results have shown that the Cys 43 and Glu 91 substitutions are responsible for the unusual behavior of HsPDF, as the replacement of these two residues by Gly and Leu, respectively, makes HsPDF as active as plant PDF1As (Table II). The side chains of residues 43 and 91 are located in close proximity (within 4.5 Å) in the crystal structure of known PDF1s (24).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…1). Our results have shown that the Cys 43 and Glu 91 substitutions are responsible for the unusual behavior of HsPDF, as the replacement of these two residues by Gly and Leu, respectively, makes HsPDF as active as plant PDF1As (Table II). The side chains of residues 43 and 91 are located in close proximity (within 4.5 Å) in the crystal structure of known PDF1s (24).…”
Section: Discussionmentioning
confidence: 92%
“…However, we cannot exclude the possibility that this domain is also involved in binding to mitoribosomes, like the additional N-terminal domain of MAP1As to cytosolic ribosomes. All animal PDFs display systematic substitutions altering crucial amino acids in motifs 1 and 2: Gly 43 , Ala 47 , and Leu 91 (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, E. coli cultured in unsupplemented medium produced Cam with 7-fold more iron than zinc, although metals analysis of the medium showed it contained 1.6 ppm of iron and 3. (21). Use of strictly anaerobic conditions to prevent oxidation also lead to the identification of Fe 2ϩ as the active site metal in the previously reported Zn 2ϩ -containing methionyl aminopeptidase from E. coli (22) (23).…”
Section: Resultsmentioning
confidence: 99%
“…11). The ferrous cation of PDF is extremely sensitive to oxidation, making the enzyme unstable (9,12). This cation can be replaced by Ni 2ϩ (9,13) or Co 2ϩ (14) to give stable variants with little or no loss of catalytic activity.…”
mentioning
confidence: 99%